The use of alteplase, although safe, does not offer clear clinical advantages when mild stroke is non-disabling - Merlino, Giovanni; Nesi, Lorenzo; Vergobbi, Pietro; Scanni, Marco Domenico; Pez, Sara; Marziali, Alessandro; Tereshko, Yan; Sportelli, Giuseppe; Lorenzut, Simone; Janes, Francesco; Gigli, Gian Luigi; Valente, Mariarosaria (Frontiers in Neurology, 2023)
Introduction It is unknown whether alteplase is effective and safe in patients with mild acute ischemic stroke (AIS). Determining whether symptoms are “disabling” or not is a crucial factor in the management of these patients. This study aimed to investigate the efficacy and safety of alteplase in patients with mild, non-disabling AIS. Methods We included all consecutive patients admitted for AIS at our institution from January 2015 to May 2022 who presented a baseline NIHSS score of 0–5 and fit the criteria to receive intravenous thrombolysis. In order to select only subjects with non-disabling AIS, we excluded patients who scored more than 1 point in the following NIHSS single items: vision, language, neglect, and single limb. Patients who scored at least 1 point in the NIHSS consciousness item were excluded as well. This study is a retrospective analysis of a prospectively collected database. Results After the application of the exclusion criteria, we included 319 patients, stratified into patients receiving and not receiving alteplase based on non-disabling symptoms. The two groups were comparable regarding demographic and clinical data. Rates of a 3-month favorable outcome, defined as a 3-month mRS score of 0–1, were similar, being 82.3% and 86.1% in the treated and untreated patients, respectively. Hemorrhagic complications and mortality occurred infrequently and were not affected by alteplase treatment. Discussion This observational study suggests that the use of alteplase, although safe, is not associated with a better outcome in highly selected patients with non-disabling AIS.